2008
DOI: 10.1002/ijc.23530
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐mediated disruption of dendritic cell function: Inhibiting the MEK1/2‐p44/42 axis restores IL‐12 production and Th1‐generation

Abstract: Disfunctional dendritic cells (DC) are common in cancer patients; however, the underlying molecular targets are poorly understood. Nevertheless, adoptive-transfer and in situ vaccination protocols continue, largely without addressing immune-suppression. Understanding tumour-mediated DC suppression would assist rational design of next generation immunotherapy. This study used a tumour-lysate loaded DC model of adoptive immunotherapy and also necrotic cells common in many tumours. Patient-derived and healthy-don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…As shown in Figure 7A, there was obviously high ERK and STAT3 activation in the DCs treated with soluble CTLA-4-Fc and CTLA-4 + BCCs compared with that in control mDCs. This was in paralleled with the result that maturation of DCs with LPS in the presence of CTLA-4-Fc resulted in robust phosphorylation of STAT3 and incubation of DCs with tumor lysates increased ERK phosphorylation [21, 22]. In contrast, the ERK and STAT3 activation were remarkably weakened in the CTLA-4 mAb-treated DCs.…”
Section: Resultssupporting
confidence: 54%
“…As shown in Figure 7A, there was obviously high ERK and STAT3 activation in the DCs treated with soluble CTLA-4-Fc and CTLA-4 + BCCs compared with that in control mDCs. This was in paralleled with the result that maturation of DCs with LPS in the presence of CTLA-4-Fc resulted in robust phosphorylation of STAT3 and incubation of DCs with tumor lysates increased ERK phosphorylation [21, 22]. In contrast, the ERK and STAT3 activation were remarkably weakened in the CTLA-4 mAb-treated DCs.…”
Section: Resultssupporting
confidence: 54%
“…7). Additionally, multiple studies have shown that increased activity of the ERK1/2 signaling pathway in DCs attenuates IL-12 and Th1 immunity while strongly inducing IL-10 secretion and therefore serving as a molecular switch in immune regulatory processes (7,52,55,56). Interestingly, we observed both reduced ERK1/2 and enhanced p38 activation in DCs upon MK2 inhibition.…”
Section: Discussionmentioning
confidence: 46%
“…IL-10 has also been reported to be involved in various other aspects of DC-T cell interaction, such as inhibiting costimulatory molecule expression (46), down-modulating MHC class II expression (47,48), or overall hindering DC maturation (49,50). Blockade of MK2 activity does not affect expression of CD80/86 (data not shown) but triggers IL-12 and IL-1a production, and hence, as shown by others and us, Th1-mediated responses (6,16,51,52). Nevertheless, in our study enhanced IL-12 secretion became evident only in the presence of T cells and was corroborated by increased levels of IL-12Rb2 and IFN-g in T cells, pointing to the involvement of additional T cell-associated signals.…”
Section: Discussionmentioning
confidence: 68%
“…Inefficiency in immune stimulation may be due to the degradation of DCs after their inoculation into the body of patients in which the specified cytokines abundantly supplied in vitro were deficient (8,9). In addition, some tumors, such as melanoma (10) and transmissible venereal tumor (11), inhibit DC function. It is therefore vital to obtain a clinical response that prevents DC degradation, and is important to promote the maturation and activation of DCs at the site of DC inoculation.…”
Section: Introductionmentioning
confidence: 99%